Effect of various LED light color on the behavior and stress response of laying hens - SULTANA, S; HASSAN, M R; CHOE, H S; KANG, M I; KIM, B S; RYU, K S (The Indian Journal of Animal Sciences, 2013)
The effects of various light emitting diode colors were observed on laying hen behavior. A total of 200 Hy-linebrown laying hens were employed, and lighting was performed as follows; white (W, control; 16 h/d), red (R; 618–635nm; 16 h/d), green (G; 515–535 nm; 16 h/d), blue (B; 455–470 nm; 16 h/d), red→green (R→G; 14 h→2 h/d), red→blue (R→B; 14 h→2 h/d), red→green→blue (R→G→B; 12 h→2 h→2 h/d) and red→blue→green (R→B→G; 12 h→2h→2 h/d) light. Behaviors were recorded as frequencies except perching behavior, which was expressed as time per hour. Hens reared in R light were more active, as expressed by greater feather pecking, ground pecking, ground scratching, and tail wagging activity than those of hens in the B light treatment. Birds spent more time perching under the B light. Feather pecking and ground scratching behaviors decreased, and preening behavior increased in frequency with age of the laying hens. On the other hand, numerically higher H: L ratio and tonic immobility duration were obtained under the R→B treatment. These results may be useful to control the behavior of laying hens.